Monitoring of nonthermal plasma degradation of phthalates by ion mobility spectrometry. Issue 7 (3rd May 2021) - Moravský, Ladislav; Michalczuk, Bartosz; Hrdá, Jana; Hamaguchi, Satoshi; Matejčík, Štefan
Abstract: Ion mobility spectrometry was used to monitor the degradation of phthalate vapors by corona discharge. Three different phthalates (dimethyl [DMP], diethyl [DEP], and dipropyl [DPP]) were examined in a corona discharge reactor (wire‐to‐cylinder geometry) at direct current positive polarity in ambient air. The relative removal efficiencies up to 96% and energetical degradation efficiencies of 229.27, 216.12, and 198.84 kJ mg −1 were achieved for DMP, DEP, and DPP, respectively. Byproducts such as methanol, ethanol, and 1‐ and 2‐propanol at extremely low densities were also detected. The identified degradation processes involved two steps: (i) An electron‐impact dissociation of phthalates into alkoxyl radicals and (ii) reactions of alkoxy radicals with water molecules to form alcohols. Abstract : Degradation of phthalates (DMP, DEP, and DPP) is carried out using nonthermal plasma (corona discharge reactor). The process of degradation and its products are detected and identified by ion mobility spectrometry. Relative removal efficiencies up to 96% are achieved in a single‐step process.